Bio-social factors and perceptions of life with quality: a challenge to the adherence of h i v patients to the antirretroviral treatment - John Harold Estrada M; Adriana Gisela Martínez P; César Ernesto Abadía B (Universidad de Antioquia, 2008)
In spite that antirretroviral therapy has contributed to improve life quality among people living with h i v, adherence to the treatment still persists as a major obstacle for therapeutic success. In order to assess the biosocial factors that contributes to adherence to this therapy by people with h i v. In order to evaluate the bio-social aspects that facilitate or obstruct the adherence to the treatment, a qualitative study combining ethnographic research, a hermeneutic approach to narratives, and a situational analysis of life experiences of people living with h i v in Colombia. Two theoretical categories were applied throughout the study: Victoria Camps' life with quality and Saussure's auto- and hetero-perception. All of the ten people who took part in the study were male patients who were attending an integral oral health program. The main factors that obstruct the adherence to the therapy were the following: 1) the discourse of the medical team loaded with biomedical jargon; 2) the dosages and side effects of the medications used in Colombia; 3) negative attitudes linked to a poor selfimage, a low social capital, and a low self-esteem; 4) low expectations in regards to a life with quality accompanied by the therapy. Among the factors that promote adherence the following were identified: 1) intra- and inter-personal negotiation processes based on the h i v serum status and the treatment; 2) knowledge about those negotiations by family members, friends, coworkers, and sentimental partners; 3) a positive perception of improvement in life quality while in treatment; 4) expectations of a life with quality depending on the adherence. Nevertheless, it was also found that those factors that contribute or impede adherence change rapidly and produce swinging in the person's mood. This mood is here understood as a complex feeling concerning life with quality in constant change, both merging individual and social aspects implied in the experience of living with h i v. It is proposed that the mood of the people is a fundamental aspect of adherence, and provided it is constantly changing it represents a challenge for assessments and proposals that aim to improve adherence.